Evaluation on carbon isotope fractionation and gas-in-place content based on pressure-holding coring technique. (1st May 2022) - Li, Wenbiao; Li, Xiao; Zhao, Shengxian; Li, Junqian; Lu, Shuangfang; Liu, Yongyang; Huang, Shan; Wang, Ziyi; Wang, Jun
Highlights: Accurate GIP content was obtained based on the pressure-holding coring technique. The accuracy of traditional methods and the CIF model were compared and verified. The CIF model can provide the most accurate estimation results of GIP content. Carbon isotope fractionation during complete degassing was observed and characterized. △ δ 13 C1 (fractionation amplitude) was demonstrated to indicate gas-adsorbed ratio. Abstract: Gas-in-place (GIP) and gas-adsorbed ratio are crucial parameters for resource potential assessment and production strategy optimization. Although various methods have been proposed to evaluate these two parameters, none have been widely recognized due to a lack of convincing comparison and validation. In this study, we established a GIP content calculation method by summing five gas components in the pressure-holding coring (PHC) technique: lost gas during retrieving, extracted gas during depressurization, lost gas during surface exposure, degassed gas, and residual gas. The GIP content of the four pressure-holding shale cores retrieved from the Longmaxi Formation of Lu-2 well, Sichuan Basin, China, ranges from 6.46 cm 3 /g to 10.58 cm 3 /g, which is used for comparing and verifying theoretical methods. The comparison results show that traditional methods, including the USBM, polynomial fit, ACF, and MCF methods, failed to accurately evaluate GIP content due to their defects in the theoretical foundation and boundary conditions settings. The carbon isotope fractionation (CIF) model derived on a rigorous theoretical basis and equipped with variable boundary conditions achieves the highest accuracy when evaluating the GIP content. Furthermore, the CIF model can determine the gas-adsorbed ratio, another critical parameter that traditional methods cannot obtain; the calculated gas-adsorbed ratio of five shale samples from the Lu-2 well is between 11.15% and 24.56%, with an average of 17.10%. With the help of the CIF model, we confirmed the general pattern of isotope fractionation during shale gas degassing and discussed the limitation and potential of two empirical parameters, δ 13 C1 of the first sample and △ δ 13 C1 (the difference in δ 13 C1 value between the last and first sample), in indicating the adsorbed gas content.